POTENSI PENERIMAAN NEGARA BUKAN PAJAK DARI LIMBAH KAYU PEMANENAN DI HUTAN ALAM DAN HUTAN TANAMAN - Astana Satria; Soenarno Soenarno; Wesman Endom (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2015)
Decline of log production forests suppress the acquisition of non-tax state revenue (PNBP) of forestry sector. To anticipate a decline in PNBP, the government is trying to raise tariffs of PSDH (forest resource provision) and DR (reforestation fund). Anticipation through tariff will affect the performance of forest management due to its impact on costs and profits. Oppositely, increases wood wastes from harvesting in natural and plantation forests have not been used optimally. This study aims to find out: (1) potential utilization of wood waste from harvesting in the forests, and (2) potential non-tax state revenues resulting from wood waste utilization. Data were collected through interviews and measurements. Interviews were conducted with forest service officers and company managers, while the measurement of wood waste was done in natural forest companies and industrial plantation forests companies, in Central Kalimantan. The collected data were analyzed quantitatively and qualitatively. If the wood waste of natural forest The result showed that harvesting by USD2/m and plantation forest harvesting by IDR284/m , the utilization of these wood wastes would raise PNBP IDR49,6 billion per year. A policy implementation method of tree length logging partularly harvesting, is recommended.